Editorial: Re-actualization in Needs (Al-Jamiah: Journal of Islamic Studies, 2005)
It seems that redefinition of Islamic fields is a must. This is due to the fact that the Islamic fields require re-actualization, so that they will be beneficial not only for Muslim themselves, but also for non- Muslim. The former group can exercise it for their recent needs, meanwhile the latter may benefit from their re-actualized spirit for their own purposes. However, the efforts of the redefinition are not without barriers. It is often that its doers are claimed as liberal or even as apostate Muslims, although they based their redefinitions on reliable Islamic references. Nevertheless, destructive criticism has not weakened their spirit to deal with it. They have even been more eager to conduct it.